Perceived factors to providing palliative care for patients with cancer - a qualitative systematic review - Haydeh Heidari; Marjan Mardani-Hamooleh; Masoud Amiri (Frontiers Media S.A., 2020)
Palliative care (PC) is one of the necessary cares given throughout a patient's experience with cancer. The aim of this study was to identify the perceived factors to providing PC for patients with cancer. Our study was a systematic review of qualitative literature. To this end, electronic databases, including CINAHL, PubMed, PsycINFO, Ovid, and Web of Science as well as Persian databases were searched and qualitative studies on the role of PC in patients with cancer published between Jan 2008 and Dec 2017 were selected. Generally, 12 studies were reviewed. A thematic synthesis approach was used to analyze the data. Exploring the selected articles, the findings on the perceived factors to providing PC for patients with cancer were categorized into three themes, including organizational factors, ethical factors, and psychological factors. This qualitative systematic review expands our knowledge about factors influencing the provision of PC for patients with cancer. It is necessary for health system managers and caregivers to pay attention to all aforesaid factors in order to improve PC for cancer patients.